Researcher trajectories, intersections, and multiple consciousness - Chan, Adrienne S. (Adult Education Discourses, 2024)
This chapter is a reflection on the places and spaces that have shaped my research and my writing. The chapter highlights my research trajectory as a researcher and academic at a university in British Columbia, Canada. Researcher positionality is a key concept in considering my researcher journey. This chapter takes a journey that is highlighted by family history, being Chinese, a settler, and a non-Indigenous researcher working with Indigenous peoples. There are tensions as well as learning experiences that are the results of working in research. These evolve into my awareness of triple consciousness, intersectionality, co-researcher relationships, and how I move forward as a facilitator for change. As a woman of colour and researcher, I examine the multiple locations that have affected my research experiences. The lessons learned from my engagement in different research projects sheds a light on how one can go forward meaningfully, making choices, as a researcher and concurrently navigate community and academic spaces. My research context draws from a focus on diversity, social justice, anti-racism, community-engaged research, and research relationships. This has led me to becoming an activist-researcher.